Strategi peningkatan kinerja SDM sebagai upaya pemulihan pariwisata pada Balkondes kawasan Borobudur - Dian Marlina Verawati; Andhatu Achsa; Ivo Novitaningtyas (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2022)
This study aims to analyze the internal and external factors of human resource performance to formulate a strategy to improve human resource performance at Balkondes in the Borobudur area to restore tourism in the new normal era. This research uses a descriptive qualitative approach. Primary data were obtained based on interview data collection methods and participatory observation. SWOT analysis, IFAS, and EFAS were used as data analysis methods. The results showed that a change in strategy was necessary. Strategy formulations for improving human resource performance include increasing the intensity of human resource training and development programs and increasing the competence of human resources to create an integrated tour package according to the needs of tourists. Moreover, management needs to provide adequate health facilities for human resources, increase cooperation with other tourism actors, and create long-term human resource development planning.